2017
DOI: 10.1038/srep43186
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties in Er3+-doped germanotellurite glasses and glass ceramics for mid-infrared laser materials

Abstract: Transparent Er3+-doped germanotellurite glass ceramics (GCs) with variable Te/Ge ratio were prepared by controllable heat-treated process. X-ray diffraction (XRD) and transmission electron microscope (TEM) confirmed the formation of nanocrystals in glass matrix. Raman spectra were used to investigate the evolution of glass structure and photon energy. Fourier transform infrared (FTIR) spectra were introduced to characterize the change of hydroxyl group (OH−) content. Enhanced 2.7 μm emission was achieved from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Besides that, there is some important and recent research activity concentrated on the study of the optical properties of tellurite glass-ceramics, considered as promising materials for lasers, especially in the near and mid-infrared 2123 . However, to the authors knowledge, laser emission in bulk tellurite glass-ceramics has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, there is some important and recent research activity concentrated on the study of the optical properties of tellurite glass-ceramics, considered as promising materials for lasers, especially in the near and mid-infrared 2123 . However, to the authors knowledge, laser emission in bulk tellurite glass-ceramics has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For the GPPr sample, the band centered in 552 cm –1 is related to bending and symmetric stretching vibration of the Ge–O–Ge of GeO 4 tetrahedral units. The band centered at 782 cm –1 corresponds to the convolution of stretching vibration modes of the Ge–O–Ge bond in GeO 6 octahedral units of germanium oxide, asymmetric stretching vibration Ge–O–Ge bridges connecting GeO 4 tetrahedral units, and antisymmetric bending vibration of the Pb–O–Pb bond in [PbO n ] units. , It was observed that the FTIR spectrum was not altered by the presence of Au NPs. After densification at 7.7 GPa, these bands shifted to lower energies, indicating an irreversible pressure-induced modification in the glass network.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al 24 demonstrated a significant improvement of the upconversion properties from Er 3+ -doped glass from the composition 70TeO 2 -15Li 2 O-15Nb 2 O 5 -0.5Er 2 O 3 (mol%) using a heat treatment at 440 • C during 5 h due to the precipitation of Li 75 Nb 1.75 Te 0.25 O 6 crystals. Kang et al 25 also demonstrated an enhancement in the intensity of the emission at 2.7 µm from Er 3+ -doped (59 10,20,30,40,50,59) after heat treatments between 400 and 610 • C for 8 h, due to the formation of lithium-and barium-based crystals. The glass with the composition 75TeO 2 -20ZnO-4Na 2 O-1Er 2 O 3 (mol%) was also reported to be promising as an enhanced intensity in the luminescence at 1.55 µm was reported after a heat treatment at 450 • C for 4 h due to the formation of Zn 2 Te 3 O 8 and Na 2 Zn 3 (CO 3 ) 4 .3H 2 O crystals.…”
Section: Introductionmentioning
confidence: 93%